2004
DOI: 10.1091/mbc.e03-07-0461
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Bbp1p in the Proper Mitotic Functions of Cdc5p inSaccharomyces cerevisiae

Abstract: The polo-box domain of the budding yeast polo kinase Cdc5p plays an essential role for targeting the catalytic activity of Cdc5p to spindle pole bodies (SPBs) and cytokinetic neck-filaments. Here, we report the isolation of Bbp1p as a polo-box interacting protein by a yeast two-hybrid screen. Bbp1p localizes to the periphery of the central plaque of the SPB and plays an important role in SPB duplication. Similarly, Cdc5p localized to the cytoplasmic periphery of the SPB. In vitro binding studies showed that Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 45 publications
(48 reference statements)
2
25
0
Order By: Relevance
“…Cdc5p localizes to the SPB in cells treated with nocodazole (data not shown), suggesting that Cdc5p localizes to the SPB in a microtubule-independent manner. It has been shown that Bbp1p, which localizes to the periphery of the central plaque and plays a critical role in SPB duplication (42), is important but not fully accountable for Cdc5p localization (35). Thus, we examined whether the proper localization of Cdc5p to the SPB requires additional components at the SPB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cdc5p localizes to the SPB in cells treated with nocodazole (data not shown), suggesting that Cdc5p localizes to the SPB in a microtubule-independent manner. It has been shown that Bbp1p, which localizes to the periphery of the central plaque and plays a critical role in SPB duplication (42), is important but not fully accountable for Cdc5p localization (35). Thus, we examined whether the proper localization of Cdc5p to the SPB requires additional components at the SPB.…”
Section: Resultsmentioning
confidence: 99%
“…Various recombinant glutathione S-transferase (GST)-fused SPB components expressed in E. coli were partially purified and used as ligands. Bbp1p, which interacts with Cdc5p both in yeast two-hybrid and in vitro analyses (35), was also expressed as a GST-fused form and included as a comparison. As observed previously (35), GST-Bbp1p, but not GST-Mps2p, interacted with Cdc5p.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…In budding yeast, Cdc5 appears to interact with multiple components within the SPB (e.g., Bbp1, Bfa1, Nud1, Spc72, etc.) (Hu et al, 2001;Ho et al, 2002;Park et al, 2004;J-E Park and KS Lee, unpublished data) and the bud-neck (e.g., Cdc11, Cdc12, Swe1, Hsl1, etc.) (Bartholomew et al, 2001;Song and Lee, 2001;Sakchaisri et al, 2004;J-E Park and KS Lee, unpublished).…”
Section: Subcellular Localization and The Polo-box Domainmentioning
confidence: 93%
“…In addition, we found that BBP1, NDC1, MPS2, KAR1, and CIN8 plasmids could all suppress the synthetic lethality to different extents ( Figure 6C). Bbp1, Mps2, and Ndc1 are all implicated in the process of inserting the newly formed SPB duplication plaque into the nuclear membrane, and they possibly have roles in anchoring the SPB once inserted (Chial et al, 1998;Schramm et al, 2000;Park et al, 2004;Araki et al, 2006). This suggests that at least part of the sfi1 C-terminal mutant phenotype could reflect a defective interaction between the SPB and the nuclear envelope.…”
Section: Genetic Interactions Of Sfi1 C-terminal Mutantsmentioning
confidence: 99%
“…The terminal phenotype of conditional alleles of these SPB components is typically a "dead" SPB, which fails to nucleate nuclear microtubules (Chial et al, 1998;Schramm et al, 2000;Park et al, 2004;Araki et al, 2006). This is due to a failure to insert the new SPB into the nuclear envelope.…”
Section: Multiple Functions For Sfi1pmentioning
confidence: 99%